Investigating mathematical investigations - Ponte, João Pedro da (2011)
There are good reasons why we may involve the students in doing mathematics investigations. Recent curricula encourage this sort of activity but we notice that its application in the classroom is not a simple matter. We discuss the issues that arise when students are presented with investigative tasks, with special interest in the dynamics of the classroom and in the role of the teacher. Our aim is to derive suggestions for classroom practice as well as for further research and teacher development.